INDONESIAN EFL TEACHERS’ CONCEPTUALIZATION OF CULTURE IN THE 21ST CENTURY EFL CLASSROOM - Ruly Morganna; Sakut Anshori (SUAR BETANG, 2018)
In dealing with the 21st century EFL pedagogy where interculturality and multiculturality are promoted to be the crucial aspects of EFL learning, this study is oriented towards investigating Indonesian EFL teachers’ conceptualization of culture in EFL classroom. The conceptualization in this sense is emphasized on their knowledge construction underlying their teaching principles. This study was conducted qualitatively by engaging three Indonesian EFL teachers selected purposively. The data of this study were garnered from open-ended questionnaires and interview. Regarding the teachers’ conceptualization, this study revealed that culture referred to the way of living becoming the framework of language use since language per se referred to a social semiotic, and the framework of learning going on inter and intra-individually. In EFL learning, culture was viewed from its interculturality. Interculturality was supported although two teachers stayed in native-speakerism specifically for linguistic competence. This study is meaningful since it serves a set of contributive knowledge vis-a-vis culture in EFL learning for EFL teachers and curriculum developers. However, this study is still delimited on cultural conception. Further studies are expected to work on the practice of cultural conception to deal with the 21st century EFL learning in Indonesia.